2000
DOI: 10.1016/s0029-7844(99)00620-1
|View full text |Cite
|
Sign up to set email alerts
|

Predicting incomplete uterine rupture with vaginal sonography during the late second trimester in women with prior cesarean

Abstract: Transvaginal ultrasonography is useful for measurement of the uterine wall after previous cesarean delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 17 publications
2
53
0
Order By: Relevance
“…The review comprises 12 studies published between 1988 and 2009 [12,[33][34][35][36][37][38][39][40][41][42][43] including together 1834 women with a previous low transverse caesarean hysterotomy who underwent ultrasound measurement of the thickness of the lower uterine segment at [35][36][37][38][39][40] gestational weeks. In seven of the 12 studies the full lower uterine segment thickness was measured [12,33,36,[38][39][40]42], in four studies the myometrial thickness was measured [34,35,37,43], and in one study both measurements were taken [41].…”
Section: Gestational Weeks Predict Uterine Rupture or Dehiscence?mentioning
confidence: 99%
See 3 more Smart Citations
“…The review comprises 12 studies published between 1988 and 2009 [12,[33][34][35][36][37][38][39][40][41][42][43] including together 1834 women with a previous low transverse caesarean hysterotomy who underwent ultrasound measurement of the thickness of the lower uterine segment at [35][36][37][38][39][40] gestational weeks. In seven of the 12 studies the full lower uterine segment thickness was measured [12,33,36,[38][39][40]42], in four studies the myometrial thickness was measured [34,35,37,43], and in one study both measurements were taken [41].…”
Section: Gestational Weeks Predict Uterine Rupture or Dehiscence?mentioning
confidence: 99%
“…In seven of the 12 studies the full lower uterine segment thickness was measured [12,33,36,[38][39][40]42], in four studies the myometrial thickness was measured [34,35,37,43], and in one study both measurements were taken [41]. Because only three of the 12 studies reported the frequency of uterine rupture separately, the outcome measure was "uterine rupture or uterine dehiscence", i.e.…”
Section: Gestational Weeks Predict Uterine Rupture or Dehiscence?mentioning
confidence: 99%
See 2 more Smart Citations
“…The benefits of a VBAC include reduced risk of thrombo-embolism, shorter duration of hospital stay, lesser requirement of blood transfusion, lower rate of postpartum fever, wound infection, uterine infection and fewer neonatal problems. 1 The present study was designed to determine whether the clinical, radio pathological and biomechanical criteria can be utilized to devise objective method for decision making regarding mode of delivery in patients with previous caesarean section without compromising maternal and fetal outcomes.…”
Section: Introductionmentioning
confidence: 99%